2007
DOI: 10.1111/j.1365-3091.2007.00871.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of across‐shelf transport of fine‐grained sediments: turbidite‐filled shelf channels in the Campanian Aberdeen Member, Book Cliffs, Utah, USA

Abstract: The shore-normal transport of fine-grained sediments by shelf turbidity currents has been the focus of intense debate over the last 20 years. Many have argued that turbidity currents are unlikely to be a major depositional agent on the shelf. However, sedimentological, architectural, stratigraphic and palaeogeographic data from the Campanian Aberdeen Member, Book Cliffs, eastern Utah suggests otherwise and clearly demonstrates that storm-generated and river flood-generated underflows can transport a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(91 citation statements)
references
References 74 publications
4
82
0
Order By: Relevance
“…Furthermore, large numbers of interpreted turbidite shelf lobes and turbidite filled channels have recently been identified in the basin (Pattison et al 2007;Hampson 2010). While it has been suggested that gutter casts may be a useful proxy for predicting down-dip occurrence of turbidites on the inner shelf (Pattison et al 2007), no detailed descriptions of models for their genesis exist. The recognition and predicted distribution of OTZe, over the more common OTZt, is important because there is a sharp permeability contrast between the better reservoir quality sandstones and the poor reservoir quality mudstones.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, large numbers of interpreted turbidite shelf lobes and turbidite filled channels have recently been identified in the basin (Pattison et al 2007;Hampson 2010). While it has been suggested that gutter casts may be a useful proxy for predicting down-dip occurrence of turbidites on the inner shelf (Pattison et al 2007), no detailed descriptions of models for their genesis exist. The recognition and predicted distribution of OTZe, over the more common OTZt, is important because there is a sharp permeability contrast between the better reservoir quality sandstones and the poor reservoir quality mudstones.…”
Section: Introductionmentioning
confidence: 99%
“…The lateral accretion surfaces indicate sustained flow. In the context of a prograding, wave-dominated shoreline fed by multiple deltas developed around fluvial input points (Charvin et al 2010;Eide et al 2014), and significant amounts of gravityflow deposits basinwards (Hampson 2010), erosively based channels within OTZ deposits with evidence for sustained flow are likely to be the deposits of subaqueous channels, cut and filled by hyperpycnal flows fed from distributary channels up-dip, and feeding shelf turbidite systems downdip (Pattison et al 2007). These channels could also be interpreted as incised valley fills, but this seems unlikely due to that there are no evidence for this interval being subject to subaerial exposure, and no evidence for contemporaneous lowstand deposits.…”
Section: Subaqueous Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Mancos Shale contains isolated sandstones and sandy intervals that were deposited as river-fed, storm-wave-modified gravity flows supplied from the west (e.g. Cole & Young 1991;Pattison 2005;Pattison et al 2007) and as nearshore deposits that were reworked towards the south by tides and waves (e.g. Boyles & Scott 1982;Hampson et al 2008).…”
Section: Geological Contextmentioning
confidence: 99%
“…The flanks of these channels are in some places seen to erode into with the surrounding offshore transition deposits, indicating that they are younger than the Kenilworth K3 parasequence. These channelized incisions are interpreted to be subaqueous channels, cut and filled by hyperpycnal flows from distributary channels updip and feeding shelf turbidite systems down-dip (Pattison et al, 2007). Further discussion about these channels is beyond the scope for this paper.…”
Section: Architectural Elements and Their Distribution Architectural mentioning
confidence: 99%